The State of Inclusion of Children with Autism Spectrum Disorder in United States Public Schools - Kelly Whalon; Mary Frances Hanline (Universidade Federal de Santa Maria (UFSM), 2013)
Legislation in the United States mandates that all children with disabilities (including those with autism spectrum disorder) have access to the general education curriculum in the least restrictive environment. Although a number of benefits associated with including children with autism spectrum disorder (ASD) in settings with their typically developing peers have been documented in the literature, skepticism remains regarding the ability of general education teachers to fully address the myriad of challenges experienced by children with ASD in these settings. This paper examines the current state of inclusion in United States Public Schools, reviews the research documenting the outcomes of the inclusion for learners with ASD, and explores arguments both supporting and questioning the role of inclusion when educating children with ASD. This paper also reviews research findings from programs that emphasize inclusion, and the educational methods that support the successful inclusion of children with ASD in general education settings.